The dock problem revisited - A. Chakrabarti; B. N. Mandal; Rupanwita Gayen (International Journal of Mathematics and Mathematical Sciences)
The well-known semi-infinite dock problem of the theory of scattering of surface water waves is reexamined and known results are recovered by utilizing a Fourier type of analysis, giving rise to Carleman-type singular integral equations over semi-infinite ranges.